Assessment of Sustainability in the Supply Chain of Sweet Red Pepper Paste Production With Exergy and Life Cycle Analyses - Samiye Adal; Zafer Erbay (Food and Energy Security)
ABSTRACT This study examines cumulative energy (CEnC), exergy (CExC), CO₂ emissions (CCO₂C), and life cycle assessment of sweet red pepper (SRP) paste production. A whole system approach in five improvement scenarios including different packaging materials and precision farming encompasses the supply chain from farm to fork and cradle to gate. The largest impact on SRP farming is caused by the use of diesel oil, the excessive use of chemical fertilizers, and the use of electricity. In SRP farming step, the CEnC is mainly caused by 86.5% fertilizer and 11% diesel usage. Hotspot impact categories were determined as abiotic (fossil) depletion potential, global warming potential, and human toxicity potential. The base case scenario has the greatest values for CEnC, CExC, and CCO₂C and impact assessment results. A CEnC value reduction of 48.6%, 50%, and 30% in the factory processing, packaging‐transportation step and whole process, respectively, is observed when the biodiesel scenario is performed. With a 40% reduction in global warming potential value, the combination of polyethylene terephthalate packaging, biodiesel, and precision farming scenario yielded the best results for each impact category analyzed in this study.